Realizing the transformative potential of conservation through the social sciences, arts and humanities. (January 2019) - Bennett, Nathan J.; Roth, Robin
Abstract: Conservation actions most often occur in peopled seascapes and landscapes. As a result, conservation decisions cannot rely solely on evidence from the natural sciences, but must also be guided by the social sciences, the arts and the humanities. However, we are concerned that too much of the current attention is on research that serves an instrumental purpose, by which we mean that the social sciences are used to justify and promote status quo conservation practices. The reasons for engaging the social sciences, as well as the arts and the humanities, go well beyond making conservation more effective. In this editorial, we briefly reflect on how expanding the types of social science research and the contributions of the arts and the humanities can help to achieve the transformative potential of conservation.